Challenges in Implementing STEM Education: Overview from Several Countries - Rizki Amalia Sa'adah; Slamet Suyanto; Nurul Faizah (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to identify various challenges encountered in implementing STEM education, as well as to describe the problems faced by several countries in implementing STEM education. To achieve the objectives of this study, the researcher conducted a literature review related to STEM education and learning, especially by conducting a Systematic Literature Review (SRL) study. This article is an SLR conducted by accessing the Scopus and Google Scholar databases as sources of information. Scopus and Google Scholar database exploration by entering the keywords "challenge" + "STEM education". The search results were exported in *CSV format (to facilitate the simulation process) and *RIS for synchronization with Mendeley. The selected articles are in the 2017-2024 period. The results of the study indicate that the challenges faced are mostly intrinsic challenges, namely the difficulty of teachers in managing learning time, as well as the lack of teachers in the STEM field who have adequate certification. Other problems were also encountered, such as the unavailability of supporting facilities for STEM education, and the lack of support from education administrators and stakeholders, which are challenges that must be considered in realizing STEM education.